2021
DOI: 10.1007/s12325-021-01883-8
|View full text |Cite
|
Sign up to set email alerts
|

Real-World Adherence to Antiretroviral Therapy Among HIV-1 Patients Across the United States

Abstract: Introduction Recent changes in antiretroviral therapies (ARTs) may have affected medication adherence of people living with human immunodeficiency virus-1 (HIV-1). In this study adherence to ART regimens among patients with HIV-1 (PWH) across the US during a recent time period was examined and study findings were stratified by US region and state. Methods A retrospective observational study using the Symphony Health Solution Integrated Dataverse database was conducted. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(24 citation statements)
references
References 18 publications
1
22
1
Order By: Relevance
“…[29][30][31] Using proportion of days covered, one US claims database study reported that 52% to 64% of PWH had ≥95% adherence, while another reported that 58% had ≥80% adherence. 32,33 By contrast, other Canadian and US claims database studies reported 86% to 93% of PWH had ≥80% adherence using proportion of days covered, similar to the ≥80% adherence rates observed in the present study. 31,32 Thus, adherence rates reported across studies using different adherence measurements vary widely, and comparisons between such studies should be interpreted with caution.…”
Section: Discussionsupporting
confidence: 86%
“…[29][30][31] Using proportion of days covered, one US claims database study reported that 52% to 64% of PWH had ≥95% adherence, while another reported that 58% had ≥80% adherence. 32,33 By contrast, other Canadian and US claims database studies reported 86% to 93% of PWH had ≥80% adherence using proportion of days covered, similar to the ≥80% adherence rates observed in the present study. 31,32 Thus, adherence rates reported across studies using different adherence measurements vary widely, and comparisons between such studies should be interpreted with caution.…”
Section: Discussionsupporting
confidence: 86%
“…There are important distinctions between the potential benefits of LAI ART as compared to LAIs for mental illness and SUD . ART adherence has been estimated at 63.4% worldwide and 74.1% in the U.S. [ 34 , 35 ]. This adherence rate is higher than estimates for patients taking oral buprenorphine (37.1–41.3%) and among patients with schizophrenia taking antipsychotics (31.5–68.7%) [ 24 , 36 ].…”
Section: Policymentioning
confidence: 99%
“…Among protease inhibitors (PIs), only darunavir, lopinavir, and saquinavir are fully active. Atazanavir, fosamprenavir, indinavir, nelfinavir, and tipranavir have reduced antiretroviral activity against HIV-2 [24, [70][71][72][73][74][75][76][77][78][79]. Effective drugs against HIV-2 are reported in Table 2.…”
Section: Treatment and Resistancementioning
confidence: 99%
“…Moreover, K65R and Q151M generate a high level of resistance for most NRTI drugs, leading to a high level of cross-resistance [89]. Regarding PI drugs, V47A is very common in the case of treatment failure with lopinavir, while V47A, I82F, and I54M have been described to cause a high level of phenotypic resistance to lopinavir and I54M for darunavir [75,76].…”
Section: Maturation Inhibitors Bevirimatmentioning
confidence: 99%